Domestic Workers amongst Paradoxes of the Politics of Gender and the Politics of Developmentalism: A Case Study from Indonesia in New Order Era - Diah Irawaty (Jurnal Perempuan, 2017)
As a political control over women to enforce them to follow state’s narrative of ideal women, the New Order regime produced and applied two contradictory forms of gender politics. On the one hand, Soeharto campaigned for state maternalism that promotes fulltime women’s role in domestic sphere. These women were claimed to be the pillar of the nation. On the other hand, the government endorsed the politics of developmentalism that carried out women in development and enforced women’s participation in the national development agendas. Women were encouraged to leave their homes and abandon their families. How was this contradictorygender politics produced, reproduced and applied toward female domestic workers? What were social-political contexts behind the deployment of this political approach? What are the implications of this politics to the situations of women’s domestic workers?